Financing issues in the rural water supply sector - Alonzo, Ruperto P. (1997)
This paper discusses the various issues related to the financing of the rural water supply sector, particularly the rationale behind national government's support for this sector before and after the implementation of the Local Government Code (LGC) of 1991. As in other developing countries, the Philippine government views safe water as a minimum basic need-thus, its continued infusion of subsidy to this sector despite the devolution of responsibilities over water supply to local government units (LGUs). But to get government support, water supply projects must be economically feasible. This paper shows how the national government should determine the extent of support it must give to LGUs in financing the capital cost of water supply. Generally, the higher an LGU's cost of capital, the higher is national government's level of support.
Keywords: Rural water supply; Government aid; Water security